Optimal dietary concentrations of vitamin C and chromium picolinate for alleviating the effect of low ambient temperature (6.2°C) on egg production, some egg characteristics, and nutrient digestibility in laying hens - Şahin, Nurhan; Şahin, Kazım (Czech Academy Agricultural Sciences, 2001)
This experiment was conducted to evaluate the effect of vitamin C (L-ascorbic acid) and chromium (chromium picolinate, Cr Pic) on egg production, some egg characteristics, and digestibility of nutrients in laying hens (Hy-Line) reared under a low ambient temperature (6.2degreesC). Two hundred and ten laying hens (32 week-old) were divided into seven groups, 30 hens per group, The treatment groups were designed in a 2 x 3 factorial arrangement using two levels of vitamin C (125 and 250 mg/kg of diet) and three levels of chromium picolinate (200, 400, or 800 mug/kg of diet), and control group was fed basal diet. The highest values of performance were obtained if 250 mg/kg vitamin C was supplemented with either 400 or 800 mug Cr per kg of diet. An interaction between vitamin C and chromium for egg production (P = 0.05) and feed efficiency (P = 0.02) was detected. Similarly, egg weight, specific gravity, egg shell thickness, egg shell weight and Haugh unit improved with diet containing 250 mg vitamin C and either 400 or 800 mug Cr per kg of diet (P less than or equal to 0.05). Digestibility of dry matter (DM), ash, organic matter (OM), crude protein (CP), and ether extract (EE) were higher with higher dietary vitamin C (P less than or equal to 0.05) and also with higher Cr (P less than or equal to 0.05). There were no interactions between vitamin C and chromium detected for any parameters measured for egg quality in terms of egg weight, specific gravidity, egg shell thickness, egg shell weight and Haugh unit and digestibility of nutrients (P greater than or equal to 0.28). Data obtained in the present study shows that a combination of 250 mg vitamin C and 400 mug chromium per kg of diet gave the best results in laying hens reared under a low ambient temperature and a conclusion is suggested that such a diet can be considered as a protective management practice in poultry to alleviate, at least in part, the depressive effect of cold stress on poultry performance.
Keywords: stress; chromium; vitamin C; performance; nutrient digestibility; laying hen